SSTUDY OF CONSTRUCTION AND ENVIRONMENTALY FRIENDLY BILIH’S (MYSTACOLEUCUS PADANGENSIS) GILLNETAT SINGKARAK LAKETUDY OF CONSTRUCTION AND ENVIRONMENTALY FRIENDLY BILIH’S (MYSTACOLEUCUS PADANGENSIS) GILLNETAT SINGKARAK LAKE - Febriani, Wina Resti; Bustari, Bustari; Brown, Arthur (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
Abstrack This research was conducted on Ocober 2019 at Singkarak Lake, West Sumatera. The purpose of this research was to identify construction, operation method, catch and environmental friendliness of gillnet. The results of research showed the construction of gillnet has 100 meters length and 6 meters depth. Gillnet construction consist as webbing, upper main line, under main line, float line, float, buoy, sinker I and sinker II. Operation of fishing gear begin with preparation, operating and handling the catch. The main catch of gillnet is bilih and by catch is kapiek. Based on result of interview conducted on 16 respondents using a weighting of 9 criteria of environmentaly friendly fishing gear according to FAO (1995). Gillnet is very environmental friendly fishing gear with score 32,0625. The result showed that there overfishing indications of bilih fish, consisting of decreased production and decreased oin catch size.Keywords: Construction, Environmental Friendly, Gillnet